2016
DOI: 10.3177/jnsv.62.366
|View full text |Cite
|
Sign up to set email alerts
|

Yolk of the Century Egg (Pidan) Contains a Readily Digestible Form of Free Vitamin B<sub>12</sub>

Abstract: SummaryIn this study, we determined the vitamin B12 content of commercially available century eggs (pidan) and characterized their vitamin B12 compositions in detail. The egg yolk and white of century eggs (each 100 g wet weight) contained 1.960.6 and 0.860.3 mg of vitamin B12, respectively. The vitamin B12 compounds purified from the egg yolk and white were identified as vitamin B 12 using liquid chromatography-electrospray ionization/tandem mass spectrometry. The vitamin B12 present in the yolk or white of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…These results imply that hypochlorous acid water could not react with food B 12 , which is present in its protein-bound form in food. 26,27 Hypochlorous acid is generated by myeloperoxidase and plays an important role in the innate immune system of mammals. 28 Nevertheless, it was suggested that highly generated hypochlorous acid leads to various diseases due to the action of a potent oxidant protein and induces chlorination and protein aggregation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These results imply that hypochlorous acid water could not react with food B 12 , which is present in its protein-bound form in food. 26,27 Hypochlorous acid is generated by myeloperoxidase and plays an important role in the innate immune system of mammals. 28 Nevertheless, it was suggested that highly generated hypochlorous acid leads to various diseases due to the action of a potent oxidant protein and induces chlorination and protein aggregation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, the pH values of the egg yolk and white are relatively low (8.6 ± 0.4 [mean ± SD] and 8.7 ± 0.5, respectively; Teng et al. 2016).…”
Section: Figmentioning
confidence: 99%
“…"Pidan" is an artificially preserved avian egg that is prevented from decomposition. According to the traditional recipes for pidan, salted duck eggs are made by immersing fresh eggs in a brine solution, and the eggs are covered with a mixture, containing salt, ash, and lime (calcium oxide as a strong base), and are maintained for several weeks before wrapping them with rice husks (Teng et al 2016). The formation of pidan is processed by the penetration of alkali through the eggshell and membrane, leading to protein denaturation and hydrolysis in the egg.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The B 12 present in the yolk of century eggs was recovered completely in macromolecular fractions. 45 However, approximately 52% of the free B 12 was formed from the century egg yolk during in vitro gastric digestion, 45 suggesting that century eggs may be a good source of B 12 .…”
Section: Eggmentioning
confidence: 99%